Conatus and Dasein: The Problem of an Existential Theory of Motivation - Markič, Marko (Conatus - Journal of Philosophy, 2021)
In the article I articulate an interpretation of the findingness (Befindlichkeit) of Dasein in Heidegger as a specific existential drive, basing it on an interpretation of his concept of existence, drawing from his earlier lectures before Being and Time, and relying on the clarification of the existential meaning of relation. Following a related interpretation of understanding and care, I offer some considerations pertaining to the problem of authentic motivation and its possible practical application. Initially, I offer an interpretation of existence as it relates to the meaning of being, understanding the relata in this ultimate sense as two aspects of speech. In this, I understand the meaning of being as a groundless call or address. Building on that, I propose a motivational understanding of findingness as the necessary drive of Dasein toward its self-interpretation as it relates to the enigmatic call of being. I supplement this view with an interpretation of existential understanding as a coequal aspect of the groundless freedom of that relation of Dasein to itself. Finally, I offer an interpretation of authenticity, in line with the aforementioned explicated understanding of existence and the corresponding meaning of the authentic motivational findingness of Dasein. In conclusion, I raise a question of how such authentic motivation could be practically understood in the perspective of life-world interactions.